1984
DOI: 10.3382/ps.0632271
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Corticosterone Concentration of Laying Hens as a Response to Increased Population Density

Abstract: The response of adrenal glands of Single Comb White Leghorn laying hens housed under different population densities was studied. The birds were reared in floor pens until they were 19 weeks of age, after which they were housed in cages. Cage size was 30.5 X 50.8 cm. Three, four, or five birds were housed per cage. Corticosterone concentrations were measured in all birds 48 and 96 hr following housing in cages and weekly thereafter for 6 weeks. Corticosterone concentrations were consistently higher in the serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
3
4

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 14 publications
3
34
3
4
Order By: Relevance
“…The results show that plasma corticosterone levels increased with increased density of the hen population, in which potentially stressful changes occur in the environmental conditions and social structure of the group (Koelkebeck et al, 1986;Gibson et al, 1986;Davami et al, 1987;Littin and Cockrem, 2001;Onbasilar and Aksoy, 2005). A significant effect of population density on corticosterone release was detected in cage systems with an available area of 310 to 520 cm 2 /bird (Edens et al, 1982;Mashaly et al, 1984). The results of the present experiment, however, are not consistent with the above-mentioned findings.…”
Section: Acta Veterinaria Hungarica 56 2008contrasting
confidence: 57%
See 1 more Smart Citation
“…The results show that plasma corticosterone levels increased with increased density of the hen population, in which potentially stressful changes occur in the environmental conditions and social structure of the group (Koelkebeck et al, 1986;Gibson et al, 1986;Davami et al, 1987;Littin and Cockrem, 2001;Onbasilar and Aksoy, 2005). A significant effect of population density on corticosterone release was detected in cage systems with an available area of 310 to 520 cm 2 /bird (Edens et al, 1982;Mashaly et al, 1984). The results of the present experiment, however, are not consistent with the above-mentioned findings.…”
Section: Acta Veterinaria Hungarica 56 2008contrasting
confidence: 57%
“…The extent of corticosterone release in laying hens is also associated with the population density on an area unit in cage technologies (Mashaly et al, 1984;Koelkebeck et al, 1986;Gibson et al, 1986;Lagadic et al, 1990;Littin and Cockrem, 2001;Onbasilar and Aksoy, 2005). Higher corticosterone levels were detected in animals kept in cages with a greater number of laying hens per area unit (Edens et al, 1982), as observed, e.g.…”
mentioning
confidence: 52%
“…Mashaly et al (1984) ao testarem três espaços na gaiola (516; 387 e 310 cm 2 /ave) observaram que as poedeiras alojadas na menor área além de apresentarem pior desempenho produtivo, tinham também comportamento mais agressivo e alteração na secreção de corticosteróide sérico.…”
Section: Característicaunclassified
“…A redução do espaço na gaiola diminui a produção e o peso dos ovos, o consumo de ração, piora a eficiência e a conversão alimentar, aumenta a mortalidade e não melhora as margens de lucro da atividade (SANDOVAL; MiLES; JACOBS,1991; CAREY; KUO; ANDERSON,1995;SOHAiL et al, 2001), além de favorecer o desencadeamento de alterações hormonais e comportamentais nas galinhas. Mashaly et al (1984) verificaram alta concentração de corticosteróide no soro sangüíneo de aves alojadas em alta densidade (310 cm 2 /ave), o que relacionaram com a resposta fisiológica ao estresse. Neste sentido, Van Hierden et al (2002) citaram que a condição de alta densidade de alojamento das galinhas leva ao aumento da agressividade e do canibalismo.…”
Section: Introductionunclassified
“…It is possible that corticosterone levels were higher in females maintained at the higher stocking rates than at lower stocking rates, and this might have had a negative influence on ovulation and subsequent oviposition. Corticosterone levels were found to be higher in laying hens housed at higher than at lower densities (Mashaly et al, 1984). Abnormal doses of corticosteroids resulted in premature LH release and irregular laying patterns in laying hens (Gilbert, 1971).…”
Section: Discussionmentioning
confidence: 99%